Caracterização funcional de HTRA1 em linhagens celulares HPV positiva e HPV negativa - Stuqui, Bruna [UNESP] (2014)
The Human Papillomavirus (HPV) is one of the most prevalent virus among sexually transmitted infections and it is associated with some malignancies. High risk HPVs contain proteins, E6 and E7, characterized by oncoproteins due to their roles in cellular transformation and suppressor tumor inactivation. One of the mechanisms used in cell transformation by E6 protein from high-risk HPVs is the interaction of its carboxy-terminal domain, known as PDZ, with PDZs domains present in some cellular proteins, triggering them to degradation. A protein that is associated with various pathological conditions and has PDZ domain is the protease HtrA1. This protein is poorly expressed in some cancers, suggesting its tumor suppressor role. The aim of this study was to evaluate the effect of the HtrA1 overexpression in HPV 16 positive (HF698) and HPV negative (C33) cell lines. The cell lines were transfected with vector containing the HTRA1 ORF or empty vector. The mRNA and protein overexpression were confirmed by qPCR and immunohistochemical, respectively. The cell lines transfected were subjected to cell proliferation, viability, apoptosis and cell cycle assays. C33 cells expressing HtrA1 presented significantly fewer colonies and showed reduced viability than cells without HtrA1 expression. On the other hand, in HPV-positive cell line there was an increase in the number of colonies in cells expressing HtrA1 and there was no difference in the cell viability assay. These results suggest that the different patterns observed between the two cell lines studied may be due to the HPV presence in HF698 and its absence in C33 cells. To confirm if the increase in the number of colonies in HPV positive cells (HF698) overexpressing HtrA1 arises from the interaction of this protein with E6, stable lines of C33 containing gene E6 were produced and subsequently performed cell proliferation assay. C33 cells overexpressing E6 and HTRA1 showed an increased number of ...